Fra én leksikalsk størrelse til mange forskellige paradigmer - Jeppesen Kragh, Kirsten; Schøsler, Lene (Ny forskning i grammatik, 2020)
We take as starting point that when lexical entities grammaticalize, they enter preexisting or new paradigms. Therefore, grammatical paradigms are important for the understanding of the reanalyses leading to grammaticalization. The lexical input that we will use to illustrate our point is the French verb voir ‘to see’, in order to show the pathway of multifunctional lexical item into grammar, i.e. into a number of individual paradigms. Our approach combines synchronic and diachronic investigations on electronic corpora. Each paradigm is based on synchronic paradigmatic analyses of functions that seem to be very ambiguous and diverse. We are convinced that paradigms provide a precise and relatively simple presentation of what otherwise would seem utterly diverse usages of a lexical entity.